Developmental, genetic and environmental variations of global DNA methylation in the first leaves emerging from the shoot apical meristem in poplar trees - A-L, Le Gac; C, Lafon-Placette; A, Delaunay; S, Maury (Plant signaling & behavior, 2019)
In the context of climate changes, clarifying the causes underlying tree phenotypic plasticity and adaptation is crucial. Studies suggest a role of epigenetic mechanisms in response to external stimuli, raising the question whether such processes can promote acclimation of trees exposed to adverse climate conditions. Recently, we revealed an environmental epigenetic footprint in the shoot apical meristem (SAM) which could partially be transmitted mitotically, for several months, up until the winter-dormant bud in field conditions. Here, we extended our previous analysis to the leaves of the same P. deltoides×P. nigra clones. We aimed at estimating the range of developmentally, genetically, and environmentally induced variations on DNA methylation. We showed that only the first leaves emerging from the SAM displayed variations of DNA methylation under changing water conditions. We also found that these variations are genotype- and pedoclimatic site-dependent. Altogether, our data raised questions and perspectives on the direct acquisition, the maintenance of environmentally induced DNA methylation changes, and their mitotic transmission from the SAM to the first emerging leaves.
Keywords: DNA Methylation; Plant Leaves; leaves; Meristem; životní prostředí; epigenetic; poplar tree; metylace DNA; genotyp; meristém; Populus; stromy; Trees; listy rostlin; drought; Environment; Genotype; DNA methylation